The role of the CHRNA4 gene in internet addiction: a case-control study - Montag, Christian; Kirsch, Peter (Journal of addiction medicine, 2012)
Recent studies from Asia provided first evidence for a molecular genetic link between serotonergic and dopaminergic neurotransmission and Internet addiction. The present report offers data on a new candidate gene in the investigation of Internet addiction-the gene coding for the nicotinic acetylcholine receptor subunit alpha 4 (CHRNA4). A case-control study was carried out. The participants were recruited from a large gene data bank, including people from the general population and from a university setting. A total of 132 participants with problematic Internet use and 132 age- and sex-matched controls participated in the study. Participants provided DNA samples and filled in the Internet Addiction Test Questionnaire. The T- variant (CC genotype) of the rs1044396 polymorphism on the CHRNA4 gene occurred significantly more frequently in the case group. Further analyses revealed that this effect was driven by females. Combined with the findings from other studies, the present data point in the direction that rs1044396 exerts pleiotropic effects on a vast range of behaviors, including cognition, emotion, and addiction.